Demystifying the key for intoxicating land finance in China: An empirical study through the lens of government expenditure. (June 2019) - Tang, Peng; Shi, Xiaoping; Gao, Jinlong; Feng, Shuyi; Qu, Futian
Highlights: An interactional framework of budgetary revenues and expenditure is proposed. Internal logics between land finance and local governments' preferences on expenditure is studied. The increase in land revenues is helpful in improving the preferences of local expenditure. Local governments' expenditure preferences will in turn increase land finance. Both of the multiplier and spillover effects of increasing expenditure are detected. Abstract: In recent decades, a sharp increase in land financing has eased the fiscal restraints that existed with regard to government expenditure in China. Introducing the land financing behaviors of local governments into the interactional framework of budgetary revenues and expenditure, this paper analyzes the influence of land finance on the preferences of local fiscal expenditure. First, we propose a theoretical hypothesis on the internal logical relationship between land finance and local governments' preferences on expenditure. Thereafter, the simultaneous equations model (SEM) is employed based on data collected upon 31 provinces between 1999 and 2014. The results imply that land finance has increased the preference for local governments' expenditure on capital construction projects while decreasing local governments' interest in public services. Moreover, even when local governments have faced policy constraints from the central state, their preferences have not significantly changed. Meanwhile, the multiplier and spillover effects of increasing expenditure upon capital construction and public services would significantly increase the potential revenues from urban land, which are recognized as an internal strengthening mechanism working between local government expenditure and land finance.